2006
DOI: 10.1007/s11934-006-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive management of upper tract urothelial carcinoma

Abstract: Recently published studies that evaluated minimally invasive treatments for upper tract urothelial cancer (UTUC) were reviewed, including adjuvant topical therapy. Ureteroscopic management remains the initial diagnostic and possibly therapeutic procedure of choice. Percutaneous management is used to treat bulky tumors or tumors that cannot be accessed ureteroscopically. Low-grade UTUC in appropriately selected patients can be safely and effectively treated endoscopically. High-grade disease tends to fail, rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this study, the recurrence rate after total NU with BCE was 13%, which is lower than the reported 20–45% rate of recurrence after incomplete ureterectomy [26–28]. Tumour stage, grade, vessel invasion and age are important factors in prognosis and survival [21,22,28–32]. Recent studies evaluated minimally invasive treatments for upper tract TCC, e.g.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, the recurrence rate after total NU with BCE was 13%, which is lower than the reported 20–45% rate of recurrence after incomplete ureterectomy [26–28]. Tumour stage, grade, vessel invasion and age are important factors in prognosis and survival [21,22,28–32]. Recent studies evaluated minimally invasive treatments for upper tract TCC, e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies evaluated minimally invasive treatments for upper tract TCC, e.g. adjuvant topical therapy [32–34]. Ureteroscopic management remains the preferred procedure for initial diagnosis and therapeutic treatment of low‐grade upper tract TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery has broadened the population of patients who are able to tolerate this surgery; however, due to concerns for preservation of renal function or inability to tolerate surgery, a selected group of patients may be suitable candidates for less-invasive management with endoscopic approach. Organ-preserving endoscopic procedures may be appropriate for patients with a solitary kidney, bilateral disease, poor renal function, or inability to tolerate major surgery [1, 2]. In addition, the indications for minimally invasive therapy have evolved to include small tumor burden, low-grade disease, or carcinoma in situ in patients with normal contralateral renal function [3].…”
Section: Introductionmentioning
confidence: 99%